ANALYSIS OF THE FEATURES OF «WAGES» DEFINITION INTERPRETATION IN THE MODERN TAXATION CONDITIONS - Абрамова, Ольга; Полтенко, Ірина; Макогон, Поліна (Socio-economic relations in the digital society, 2019)
The rational organization of remuneration and its correct defi nition effects not only on the enterprise efficiency, but also on a decent standard of population living level. The analysis of publications has shown that the issue of remuneration requires an improvement in line with current economic requirements. The whole society is interested in the process of creating a competitive product, but it is possible to separate the three parties directly involved: there are the producer, the employee and the state as the regulator of legal, economic and social relations. A wider defi nition of wages is proposed that will refl ect the current realities of market competition and determine the interests of not only two stakeholders — the employee and employer, but, in general, of three subjects of the national economy social and labor relations: the population represented by workers, entrepreneurs and institutions and the state. In the production process the state is represented by its authorized bodies for the regulation of relations between producers and their employees, and also is interested in increasing the income of both parties for the purpose of taxation and social protection. Thus, wages are an economic category that: 1) characterizes the relationship between the employer and the employee in the distribution process of the newly created value, motivation and payment of remuneration performed in accordance with the terms of the employment contract, as well as paymentof the compulsory state social insurance amount in accordance with the laws; 2) reflects the market value of labor employment and the main taxable part of the employee’s labor income, obtained as a result of the implementation of his labor capacity and which should ensure the necessary reproduction of manpower, decent standard of living and social protection, both presently and in the future. Th e expediency of a two-stage defi nition of the defi nition of «wages» is substantiated, which, in contrast to existing interpretations, reveals the essence of relations and corresponds to a systematic approach to economic categories’ definitions.
Keywords: wages; definition; taxation; social and labor relations; state